Interpersonal teaching style. A profile analysis according to the differences in motivation, basic psychological needs, school climate and teaching with satisfaction - Manzano Sánchez, David; Jiménez-Parra, José Francisco (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
This study analyzes the differences in psychosocial variables as a function of the interpersonal teaching style in Secondary Education students. This descriptive cross-sectional study was carried out with a sample consisted of 120 students, aged 12 to 17 years (M = 13.4, SD = 1.36). A battery of validated questionnaires was completed to analyze motivation, basic psychological needs, school social climate, sports satisfaction and the teaching interpersonal style, which acted as a variable to elaborate the cluster profiles. The analysis of the dendrogram suggested the creation of two profiles, the first, “high autonomy support” and the second, “high controlling style”. The multivariate analysis showed higher values ​​for the first profile in autonomy, competence, social relationship, teacher climate and fun, while the second profile being higher in amotivation and boredom. It is concluded that greater support for autonomy allowed greater satisfaction of the adaptive psychological variables.